Toxocariasis in Children: An Update on Clinical Manifestations, Diagnosis, and Treatment - El-Sayed, Nagwa Mostafa; Ramadan, Manar Ezzelarab (Journal of Pediatric Infectious Diseases, 2017)
Toxocariasis, a parasitic infection, carries a major health risk in children, especially in the developing countries. Children are the most infected group because of their undeveloped immune system, their higher exposure to infection, and the frequency of reinfections depending on the factors related to their hygienic and behavioral habits. Many human infections are asymptomatic, with only eosinophilia and positive serology. However, several complications were associated with this neglected disease. These complications depend on the organs invaded by migrating Toxocara larvae, the degree of the larvae burden, and the strength of the host immune response. This review aims at giving an update on clinical manifestations, diagnosis, and treatment of toxocariasis in children. The pediatricians should merge this information into their clinical diagnosis to defeat this neglected disease by establishing the correct diagnosis and treatment.
Keywords: toxocariasis; children; clinical manifestations; diagnosis; treatment